PENANAMAN SIKAP SOSIAL MELALUI PEMBELAJARAN IPS PADA SISWA KELAS IV SD NEGERI 17 TANJUNG BATU - Dama Rizka Zakillah; Murjainah; M. Taheri Akhbar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to describe: the results of instilling social attitudes in fourth grade students of SD Negeri 17 Tanjung Batu through social studies learning. This research is a descriptive qualitative study of cultivating social attitudes in grade IV students of SD Negeri 17 Tanjung Batu through Social Studies learning which was collected through observation and interviews as well as documentation. The data analysis used is the Miles and Huberman Model which consists of data collection, data reduction, data display and conclusion drawing or verification. The results of the study showed that: the social attitudes of fourth grade students at SD Negeri 17 Tanjung Batu were instilled through social studies learning by instilling the values ​​of students' social attitudes with social studies learning strategies, the teacher's ability to give examples of good interaction attitudes to students both in the classroom as well as outside the classroom, associating social studies subject matter with the values ​​of social attitudes and by providing positive sentences that contain social attitude values ​​at the beginning of learning, using social studies learning IT media, and conducting evaluations related to social attitudes. The results of inculcating social attitudes of class IV students at SD Negeri 17 Tanjung Batu through social studies learning have been embedded in the Good category. The teacher seems to have succeeded in instilling the value of social attitudes in accordance with the indicators that the researcher has described, namely: discipline, vocational, and tolerance in fourth grade students at SD Negeri 17 Tanjung Batu.